Examples in the development of Clementi’s four-hand piano sonata - MUREȘAN, Valentin (Studia Universitatis Babes-Bolyai Musica, 2023)
Muzio Clementi exploits the possibilities of duet texture more, individualizing the middle voices as a separate layer. However, it cannot compete with the refinement of the interweaving of voices in Mozart’s duets. The bass and middle voices often provide a supporting function for the melodic material concentrated in the primo part. Clementi’s four-hand sonatas are among the earliest significant works of four-hand piano in musical history. They reflect the composer’s individual and intense journey through the genre and the variety of his approaches.